Choroidal thickness in eyes of rheumatoid arthritis patients measured using optical coherence tomography: A systematic review and meta-analysis - Fekrazad, Sepehr; Shahrabi Farahani, Mohammad; Salehi, Mohammad Amin; Hassanzadeh, Golnar; Arevalo, J. Fernando (Survey of ophthalmology, 2024)
Rheumatoid arthritis (RA), an autoimmune disease, affects eyes in 25% of cases. Retinal alterations in RA can function as biomarkers as early risk indicators for developing sight-threatening conditions. Optical coherence tomography (OCT) provides high-resolution images of the retina and its component’s thickness measures. The purpose of this review is to compare the choroidal thickness (CT) of RA patients and healthy controls. We examined the databases of PubMed, Scopus, and Embase. Depending on the heterogeneity, an appropriate model was used for the meta-analysis. Additionally, meta-regression, publication bias, subgroup analyses, and quality evaluation were carried out. We evaluated 8 studies involving 363 RA patients and 343 healthy controls. Our findings demonstrated that RA participants had significantly lower CT at 500 and 1500 µm nasal and temporal to the fovea compared to controls. The subfoveal, 1000 µm temporal and nasal to the fovea, and average CT, however, did not demonstrate statistical significance. The results of this study demonstrate that choroidal thickness is different in RA patients from healthy controls in several areas. OCT measurements may be related to both the visual acuity and the possibility of developing several rheumatic-ophthalmic problems. Future research is thus needed to get more firm findings. •We provide a systematic review of the current literature on choroidal thickness in RA subjects.•RA patients show thinner choroid thickness at 500 µm and 1500 µm nasal, and temporal to the fovea.•RA patients with more severity develop thinner choroidal thickness.•We discuss the limitations of the current text and provide directions for future RA research.